A Statistical Study of Magnetopause Boundary Layer Energetic Electron Enhancements Using MMS - Chepuri, S. N. F.; Jaynes, A. N.; Baker, D. N.; Mauk, B. H.; Cohen, I. J.; Leonard, T.; Turner, D. L.; Blake, J.B.; Fennel, J.F.; Phan, T. D. (Frontiers in Astronomy and Space Sciences, 2022)
We took a survey of boundary layer (or low-latitude boundary layer) crossings by the Magnetospheric Multiscale (MMS) mission. Out of 250 total crossings, about half showed enhancements of high-energy (>30 keV) electrons in the FEEPS sensor and a little less than half of those energetic electron events had whistler-mode waves present. Energetic electron enhancements were more likely to be present at magnetic local times closer to noon and at distances of less than about 20 Earth radii, but there was seemingly no correlation with magnetic latitude. For almost all of these events, the pitch angles of the FEEPS electrons were peaked at 90 or isotropic, not field-aligned. Most of the events for which we had data to make a determination showed either direct or indirect evidence of reconnection. Overall, energetic electron enhancements are a fairly common occurrence and there appears to be some connection between whistler waves, energetic electron enhancements, and reconnection, whether it is a direct link or some other process affecting all of them.